Ex-vivo Kidney Machine Perfusion: Therapeutic Potential - Zulpaite, Ruta; Miknevicius, Povilas; Leber, Bettina; Strupas, Kestutis; Stiegler, Philipp; Schemmer, Peter (Frontiers in Medicine, 2021)
Kidney transplantation remains the gold standard treatment for patients suffering from end-stage kidney disease. To meet the constantly growing organ demands grafts donated after circulatory death (DCD) or retrieved from extended criteria donors (ECD) are increasingly utilized. Not surprisingly, usage of those organs is challenging due to their susceptibility to ischemia-reperfusion injury, high immunogenicity, and demanding immune regulation after implantation. Lately, a lot of effort has been put into improvement of kidney preservation strategies. After demonstrating a definite advantage over static cold storage in reduction of delayed graft function rates in randomized-controlled clinical trials, hypothermic machine perfusion has already found its place in clinical practice of renal kidney transplantation. Nevertheless, an active investigation of perfusion variables, such as temperature (normothermic or subnormothermic), oxygen supply and perfusate composition, is already bringing evidence that ex-vivo machine perfusion has a potential not only to maintain kidney viability, but also serve as a platform for organ conditioning, targeted treatment and even improve its quality. Many different therapies, including pharmacological agents, gene therapy, mesenchymal stromal cells or nanoparticles (NPs), have been successfully delivered directly to the kidney during ex-vivo machine perfusion in experimental models, making a big step towards achievement of two main goals in transplant surgery: minimization of graft ischemia-reperfusion injury and reduction of immunogenicity (or even reaching tolerance). In this comprehensive review current state of evidence regarding ex-vivo kidney machine perfusion and its capacity in kidney graft treatment is presented. Moreover, challenges in application of these novel techniques in clinical practice are discussed.